(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The article discusses the most important aspects of the above-ground rights in Germany by focusing its social function. It initiates the investigations with a brief historical study, in which are highlighted the peculiarities of its development. The work conducts an examination of the matter in Germany, highlighting some points such as: legal nature, practical use, areas of use, social character, establishment, transfer and extinction of that right. Finally, the work questions the non-use of the institute in Brazil, which can be rethought if we consider the German example, especially with regard to its possible social aspect.